2013
DOI: 10.4103/0973-8258.116383
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic potential of alkaloids of Tribulus terrestris L. against some pathogenic microorganisms

Abstract: Context: Antibiotic resistance has become a global concern. There has been an increasing incidence of multiple resistances in human pathogenic microorganisms in recent years, largely due to indiscriminate use of commercial antimicrobial drugs commonly employed in the treatment of infectious diseases. Tribulus terrestris (Family: Zygophyllaceae) is a well-known medicinal plant and has been used world-wide for the treatment of infectious diseases. Alkaloids are group of naturally occurring chemical compounds, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…There are several in vitro studies that have revealed the antibacterial potency of TT total or fractionated extracts on Gram-negative and Gram-positive bacterial strains. Among the Gram-positive bacteria, facultative anaerobe strains such as Staphylococcus aureus, Streptoccocus mutans, Streptococcus sanguinis, Actinomyces viscosus, Enteroccocus faecalis, and Bacillus subtilis were susceptible and among the Gram-negative bacteria Escherichia coli, Salmonella typhi, Proteus mirabilis, and Klebsiella pneumoniae were susceptible [87][88][89][90][91][92]. It is still unclear which components are responsible for the antibacterial activity, but alkaloids contribute to the general antibacterial effect of the total extracts [88].…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…There are several in vitro studies that have revealed the antibacterial potency of TT total or fractionated extracts on Gram-negative and Gram-positive bacterial strains. Among the Gram-positive bacteria, facultative anaerobe strains such as Staphylococcus aureus, Streptoccocus mutans, Streptococcus sanguinis, Actinomyces viscosus, Enteroccocus faecalis, and Bacillus subtilis were susceptible and among the Gram-negative bacteria Escherichia coli, Salmonella typhi, Proteus mirabilis, and Klebsiella pneumoniae were susceptible [87][88][89][90][91][92]. It is still unclear which components are responsible for the antibacterial activity, but alkaloids contribute to the general antibacterial effect of the total extracts [88].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Among the Gram-positive bacteria, facultative anaerobe strains such as Staphylococcus aureus, Streptoccocus mutans, Streptococcus sanguinis, Actinomyces viscosus, Enteroccocus faecalis, and Bacillus subtilis were susceptible and among the Gram-negative bacteria Escherichia coli, Salmonella typhi, Proteus mirabilis, and Klebsiella pneumoniae were susceptible [87][88][89][90][91][92]. It is still unclear which components are responsible for the antibacterial activity, but alkaloids contribute to the general antibacterial effect of the total extracts [88]. The antibacterial effects of saponins are well documented and the mechanism of action is based on the destruction of the cell membrane, leading to cell death (bactericidal effect), probably due to their amphiphilic nature and their surfactant properties.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…MIC of cmde alkaloid to S. aureus in this study was lower than MIC of ethanolic extract of papaya leaves found by Rahman et al (31), i.e., in a concentration of 1.25 mg/ml. This crude alkaloid MIC was also lower than the crude alkaloid extract from Tribulus terrestris leaves against S. aureus that was in a concentration of 0.625 mg/ml (16). On the other hand, a MIC of papaya leaf crude alkaloid extract was higher than that of the alkaloid extract from Aconitum elwesii and Sida acuta Burm.…”
Section: Mic Of Crude Alkaloid Of Papaya Leaves To S Aureusmentioning
confidence: 68%
“… [ 7 , 35 ] 5 Flavonoids (Kaempferol-3-glucoside Tribuloside, Kaempferol, and Kaempferol-3-rutinoside Fruit Aphrodisiac Diuretic, Anti-spasmodic and Antioxidant [ 99 , 138 ] 6 Alkaloids (Tribulusterine, Tribulusamide, Tribulusin, Harmine, Harmmol, Terrestriamide and Terrestribisamide, Fruit Antibacterial Antioxidant and Aphrodisiac. [ 84 , 139 ] 7 Saponins, Phytosterols, Rutin, Tannins, Protodioscin, Tannins, Arginine, Carbohydrates, β-carboline Alkaloid and Tribulusin, Stem Immunomodulatory effects, Anti-Spasmodic and Antioxidant, [ 7 ] 8 Tribulus Terrestris roots have entirely reducing sugar properties; Flavonoids, Saponins, alkaloids, Triterpenoids, Xanthoprotein, and Unique phenolic compounds are phenol 2-(5,6-dimthyl pyrazinyl), and Histidine. Root Aphrodisiac, Ant- bilious, and Antidiabetic.…”
Section: Phytochemistrymentioning
confidence: 99%